Entrepreneurship Development of Beneficiary Families from Program Keluarga Harapan (PKH) through Village-Owned Enterprises (Study at Village-Owned Enterprise Karya Mekar Sukajadi Cianjur) - Mochammad Ikbal Sonuari; Fentiny Nugroho (Soshum: Jurnal Sosial dan Humaniora, 2021)
This research discusses the entrepreneurship development of beneficiaries which is carried out through the BUMDes institution. The BUMDes chosen is BUMDes Karya Mekar, which is one of the BUMDes that involves the beneficiaries of the Family Hope Program in the BUMDes business. Located in the area of ​​Sukajadi Village, Campaka District, Cianjur Regency. This research uses a qualitative approach with a descriptive research type. The research objective is to describe the input, process, and output in entrepreneurship for beneficiaries through BUMDes. Data collection methods used are through interviews, observation, and documentation studies. The results showed that the entrepreneurship development of beneficiaries through BUMDes can be seen from the input (environmental factors, individuals, organizations), process (alignment of resources), and output (organizational, individual, and community benefits), the three of which are a series that are inseparable from one another. This research brings the benefit that the presence of KPM PKH has made BUMDes a pillar of economic activity in the village that can function as a social or commercial institution. Entrepreneurship development for KPM PKH through BUMDes has created KPM PKH entrepreneurs in the future. BUMDes is expected to be able to increase community efforts in managing the economic potential of the Village.